Al-Si Alloys Automotive, Aeronautical, and Aerospace Applications - Robles Hernandez, Francisco C.; Herrera Ramírez, Jose Martin; Mackay, Robert (Springer International Publishing : Imprint: Springer, 2017)
This book details aluminum alloys with special focus on the aluminum silicon (Al‐Si) systems - that are the most abundant alloys second only to steel. The authors include a description of the manufacturing principles, thermodynamics, and other main characteristics of Al‐Si alloys. Principles of processing, testing, and in particular applications in the Automotive, Aeronautical and Aerospace fields are addressed. Discusses aluminum silicon alloy selection, manufacturing, applications with particular attention to the issues of mechanical properties and soundness; Includes key technologies for aluminum silicon alloys such as casting, chemical and electromagnetic processing, casting, powder metallurgy, and applications for automotive,  and aerospace use; Addresses both, hypo and hypereutectic, alloys and their applications in-depth.